Problems of European economic integration - BAFFI, P. (PSL Quarterly Review, 2014)
The author reconstructs the recent experience of the free-trade area in Europe, and draws four main scenarios for the future. Great gains in productivity and a marked acceleration of economic expansion are not to be expected from further European economic integration. However, establishing permanent economic bonds implies the avoidance of beggar-thy-neighbour policies that the future may hold in store. The Common Market countries are proceeding faster than was previously expected, even though the farther they go, the more difficult negotiations will become. For example, problems are inevitable in the process of merging high price markets for farm products in the six Common Market countries and the British low price system. JEL: F15, E30